Identification of a novel homozygous mutation in MYO3A in a Chinese family with DFNB30 non-syndromic hearing impairment. (May 2016) - Qu, Ronggui; Sang, Qing; Xu, Yao; Feng, Ruizhi; Jin, Li; He, Lin; Wang, Lei
Abstract: Introduction: Hearing loss is a common sensory impairment. Several genetic loci or genes responsible for non-syndrome hearing loss have been identified, including the well-known deafness genes GJB2, MT-RNR1 and SLC26A4. MYO3A belongs to the myosin superfamily. Previously only three mutations in this gene have been found in an Isreali family with DFNB30, in which patients demonstrated progressive hearing loss. Methods: In this study, we characterized a consanguineous Kazakh family with congenital hearing loss. By targeted sequence capture and next-generation sequencing, we identified a homozygous mutation and did bioinformatics analysis to this mutation. Results: A homozygous mutation, MYO3A:c.1841C>T (p.S614F), was identified to be responsible for the disease. Ser614 is located in the motor domain of MYO3A that is highly conserved among different species. Molecular modeling predicts that the conserved Ser614 may play an important role in maintaining the stability of β-sheet and the interaction between neighboring β-strand. Conclusions: This is the second report on MYO3A mutations in deafness and the first report in China. The finding help facilitate establishing a better relationship between MYO3A mutation and hearing phenotypes.